Proceso de Optimización y Evaluación de una Antena Micro-coaxial para el Tratamiento de Tumores Óseos - Rojas Hernández, Sonia; López Camacho, José; Trujillo Romero, Citlalli Jessica (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Bone tumors are commonly treated with surgery (amputation), radiation therapy, and chemotherapy; however, its side effects compromise the patient’ quality of life. Thermotherapy is a less aggressive alternative to treat these tumors. In thermal ablation temperatures between 60 °C-100 °C must be reached in the tumor. The process to design and optimize a one-slot microwave antenna by using COMSOL Multiphysics, is proposed. An axi-symmetric 2D parametric study was carried out, in which 576 scenarios (antenna designs) were analyzed to choose the one that allowed higher energy transmission, temperature increases in the ablation range, larger areas of necrotic tissue, etc. From this study, the best scenario was chosen to evaluate its performance by using a 3D anatomical model. The final optimized antenna presented a SWR = 1.45; moreover, it was possible to observed that the 67.35% of tumor volume reaches ablation temperatures.